(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2015)
In the article the author studied the definitions of fiscal policy and showed essence of fiscal policy at the local level, offered the fiscal policiy should observe the following principles at the local level : independence, transparency, effectiveness, subsidiarity, social justice, objectivity, balance, continuity, reporting and undivided responsibility, fiscal equivalence exchange.